Pattern of EthnicCoalition in Regional Head Election: Evidence from Indonesia - Supriatna, Encup; Dulkiah, Moh.; Irwandi; Leonardo Sari, Avid; Ismail (International Journal of Psychosocial Rehabilitation, 2020)
This study discusses the ethnic coalition in regional head elections in Belitung Regency, Indonesia. Local politics in Belitung Regency contains ethnic identity politics. These identity politics involve three ethnic groups, namely Malays (as the ethnic majority), Chinese, and Bugis (as ethnic minorities). The competition of the three ethnic groups became more open in the current era of regional autonomy triggered by direct regional head elections. Changes in political controversy in post-reform Indonesia in 1998 have opened up a large space to fight for group-based interests, especially for minority groups. In this situation, primordialism is no longer seen as something that must be abandoned, but rather effective to be used as a symbol and political language in order to gain legitimacy and sympathy in the process of gaining power. This study uses a qualitative approach. The results of the study show that the right ethnic coalition will make the candidate’s chances of winning the contestation of regional head elections bigger. Ethnic minority groups can win the contestation of regional head elections when in coalition with the ethnic majority. The majority of ethnicities who pair up with the majority ethnic group have a small chance of victory. This study concludes that ethnic collaboration is the main preference in determining candidates for regional heads in Belitung Regency.